The nature of interaction in pedagogical situation - Dobrova, Victoria V. (Vestnik of Samara State Technical University Psychological and Pedagogical Sciences, 2023)
The paper examines in detail the essence and specificity of the process of pedagogical interaction within the boundaries of a pedagogical situation. Since the concept of "pedagogical situation" both in literature and in practice is interpreted too arbitrarily, on the basis of our research we proposed our own definition of the concept of "pedagogical situation" as a process of pedagogical interaction between the subjects of pedagogical activity, within the framework of which a single pedagogical task of translating a unit of culture is solved in specially organized pedagogical conditions and space-time continuum. The pedagogical process is a developing interaction of its subjects aimed at solving educational tasks. The usual system of teaching turns out to be oriented to subject-object interaction, in which the positions of the teacher and the student are in disequilibrium. Modern pedagogy is focused on the organization of subject-subject interactions, in which both teacher and student are subjects, collaborators in joint cognitive activity. It is shown that the student is a subject, appearing as an object of educational influence; this paradoxical relation of the participants of the situation represents the dialectics of the pedagogical process. Pedagogical situation is always focused on the interaction of one person, performing pedagogical functions, with another person for the purpose of his/her development and improvement, it determines the nature of emerging and developing relations of the subjects.